Concepções de professores de educação superior de uma instituição privada de São Paulo sobre o currículo integrado - Giora, Kalinka (2019)
This study aims to identify and understand the professors’ comprehension integrated curricula. The research participants are Professors at Bachelor's courses in Business Administration, Accounting Sciences, Economic Sciences and Law, as well as in the Courses in Foreign Trade Technology, Commercial Management, Financial Management, Logistics, Marketing and Human Resources Management at a private education institution in the city of São Paulo. The choice of this institution is due to its recognized undertaking in adopting integrated curricula for Education at tertiary level. Davini's (1999) integrated curriculum definition was used to support the study. In a universe of 60 professors, the research was attended by 27 professors. The instrument of collection was an electronic questionnaire that conjugated the technique of free evocation of words to the discursive questions. To the participants of the investigation, information of sociocultural profile was also requested. The collected information was systematized and considered in light of the content analysis. Sociocultural profile information was quantified. Empirical data, associated with the literature review, contributed to the understanding of teachers' conceptions of the integrated curriculum. From the study undertaken, it is possible to affirm that the proposal of curricular integration of the institution researched is consistent, however part of the teachers still anchors their conceptions integrated curriculum in traditions of educational practice. Based on the information collected, the hypothesis was raised that, although the IES promoted weekly meetings by courses, or areas (Colegiados de Curso / Núcleo Docente Estruturante), even so, such training does not reach most of the teachers, which prevents the collective construction of integrated curricula. Teachers recognize the importance of collective work for curricular integration, however, the development of Integrated Projects and Integrated Assessments has not been pointed out as an integrator of Curricular Units. In this respect, it should be noted that some teachers have demonstrated that they do not have elements that allow the elaboration of a precise conception about curricular integration. For them, curricular integration is still understood as a challenge and a novelty. By studying teachers' conceptions, it was possible to understand how they can guide their practices. In this sense, it is emphasized that, for the development of an integrated curriculum, responsibility cannot rest solely on the teacher, since it is necessary to stimulate the construction of a new educational culture by the higher education institution, with investment in pedagogical training and in the transformation of traditional knowledge of the entire academic community.